Waterborne polymers as kinetic/anti-agglomerant methane hydrate and corrosion inhibitors: A new and promising strategy for flow assurance - Farhadian A.; Varfolomeev M.A.; Kudbanov A.; Rezaeisadat M.; Nurgaliev D.K. (2020)
© 2020 Elsevier B.V. This study introduces a novel and promising strategy based on waterborne polymers for hydrate and corrosion risk management and incompatibility issues between them. The results demonstrated a good performance of waterborne polyurea/urethanes (WPUUs) in delaying the induction time (up to 17 times) and reducing the hydrate growth rate (up to 7.7 times) compared to water. Moreover, the hydrates formed in the WPUUs system at water-cut 60% were uniformly dispersed in the liquid phase like slurry and they are particularly appropriate for the flow in the pipelines. In addition, the weight loss, SEM-EDX, profilometer, and quantum chemical studies showed that the WPUUs suppress the corrosion process in a severely corrosive environment (2 M HCl). This research reports for the first time the satisfactory reasons for using waterborne polymers as a promising kinetic/anti-agglomerant methane hydrate and corrosion inhibitors and will develop new opportunities in the field of hydrate and corrosion risk management.